Suitability of Community based Mangrove Ecotourism Land in Lelilef Waibulan Village, Weda Tengah District - Ismail, Hamid; Kurniawan, Andy; Sujud, Suratman; Hadun, Ramli; Sofyan, Adnan; Umasugi, Buhari; Sapsuha, Yusri; Abubakar, Salim (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The development of mangrove ecotourism is one of the efforts to utilize environmental services from coastal areas sustainably. Ecotourism in mangrove forests is seen as being able to synergize with real forest ecosystem conservation measures. The purpose of the study was to determine the suitability of community-based mangrove ecotourism land in Lelilef Waibulan Village, Weda Tengah District based on ecological, socio-economic and supporting aspects. Data collection procedures include observations of biophysical conditions (mangrove vegetation, biota objects, tides), interviews with interviews using Purposive sampling techniques. The results of the study obtained the mangrove forest area of Lelilef Waibulan Village is very suitable to be developed as a mangrove ecotourism area both from ecological, socio-economic and supporting aspects.